The material, moral, and affective worlds of dealing and crime among young men entrenched in an inner city drug scene - Fast, Danya (Int J Drug Policy, 2017)
A large body of previous research has elucidated how involvement in drug dealing and crime among marginalized urban youth who use drugs is shaped by the imperatives of addiction and survival in the context of poverty. However, a growing body of research has examined how youth’s involvement in these activities is shaped by more expansive desires and moralities. In this paper, we examine the material, moral, and affective worlds of loosely gang affiliated, street level dealing and crime among one group of young men in Vancouver, Canada. Drawing on longitudinal interviews with 44 young men from 2008 to 2016, and ethnographic fieldwork with a group of approximately 15 of those young men over the same time period, we argue that for these youth, dealing and crime were not solely about economic survival, or even the accrual of highly meaningful forms of “street capital” in the margins. Rather, as “regimes of living,” dealing and crime also opened up new value systems, moral logics, and affects in relation to the tremendous risks, potential rewards, and crushing boredom of life in the margins. These activities were also understood as a way into deeply desired forms of social spatial belonging in the city, which had previously only been imagined. However, across time dealing and crime ultimately “embedded” young men in cycles of incarceration, destitution, addictions, and mental health crises that ultimately reinforced their exclusion – from legal employment, but also within the world of crime. The findings of this study underscore the importance of adopting a life course perspective in order to meaningfully address the harms associated with involvement in dealing and crime among youth in our setting.